Mechanism and clinical progression of solid tumors bone marrow metastasis - Yang, Ruohan; Jia, Lin; Cui, Jiuwei (Frontiers in Pharmacology, 2024)
The rich blood supply of the bone marrow provides favorable conditions for tumor cell proliferation and growth. In the disease's early stages, circulating tumor cells can escape to the bone marrow and form imperceptible micro metastases. These tumor cells may be reactivated to regain the ability to grow aggressively and eventually develop into visible metastases. Symptomatic bone marrow metastases with abnormal hematopoiesis solid tumor metastases are rare and have poor prognoses. Treatment options are carefully chosen because of the suppression of bone marrow function. In this review, we summarized the mechanisms involved in developing bone marrow metastases from tumor cells and the clinical features, treatment options, and prognosis of patients with symptomatic bone marrow metastases from different solid tumors reported in the literature.